CASE- METHODOLOGY FOR TRAINING THE SCIENTIFIC PEDAGOGICAL STAFF FOR SERVICES OF A DIGITAL LIBRARY - Novytska, Т.Л. (Journal of Information Technologies in Education (ITE), 2015)
This article describes a technique using a case method in preparing teaching staff to use digital library services as an example of a training exercise. It has been suggested program, which will be trained users, editors and administrators DL. Developed scale assessment of knowledge and skills of teaching staff for the results of card problems. Created test questions for the training sessions. Discovered the case-method as type of learning method. Discovered the basic characteristics of situational teaching method: analytical and cognitive. Analytical activities may include problem analysis and/or systems analysis and/or causal analysis, and/or praxeological analysis, and/or prognostic analysis and/or target-oriented analysis. Investigated the principle of formation of bibliographic descriptions DL resource based metadata concept of «quality metadata DL». Proved that mistake when making metadata may somehow block access to the DL.